Các sản phẩm dạng thư mục và ý nghĩa của chúng - Vũ, Duy Hiệp (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Deals with products in the form of bibliographies and their significance; presents scientific citation indexex and their application to scientific statistics, publishing and development of information resources